2013
DOI: 10.1111/cob.12034
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of New Onset substance use disorders among post‐weight loss surgery patients

Abstract: Overall, findings suggest that post-WLS patients are overrepresented in substance abuse treatment programmes, and the majority of them report no history of SUD before WLS. Relative to non-WLS patients in SUD treatment, post-WLS patients in substance abuse treatment are disproportionally diagnosed with alcohol dependence, including alcohol withdrawal. Post-WLS patients may be at elevated risk for development of New Onset SUD in the absence of a prior SUD history; this group is phenotypically different from thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 20 publications
3
21
0
1
Order By: Relevance
“…Saules et al (2010) found that among 35.8% of 54 (mean age= 44.6 ± 9.1) postoperative substance users had a history of heavy use of drugs and/or alcohol and 43.4% of them were new-onset heavy users, while 20.8% of preoperative heavy users switched to a different drug and/or alcohol after surgery than they used before surgery. Similarly, Ivezaj et al (2014) and Wiedemann et al (2013) reported that the percentage of new-onset SUD was 68% and 60%, respectively. Wiedemann et al also found that patients with a preoperative SUD history tended to use more types of substances than new-onset SUD patients.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Saules et al (2010) found that among 35.8% of 54 (mean age= 44.6 ± 9.1) postoperative substance users had a history of heavy use of drugs and/or alcohol and 43.4% of them were new-onset heavy users, while 20.8% of preoperative heavy users switched to a different drug and/or alcohol after surgery than they used before surgery. Similarly, Ivezaj et al (2014) and Wiedemann et al (2013) reported that the percentage of new-onset SUD was 68% and 60%, respectively. Wiedemann et al also found that patients with a preoperative SUD history tended to use more types of substances than new-onset SUD patients.…”
Section: Resultsmentioning
confidence: 87%
“…Among adults with no prior use history, certain types of drugs (opiate, benzodiazepine) were more likely to be initiated after surgery compared to alcohol and cigarettes (Saules et al, 2010). Relapsed users tended to use more types of substances (including initiating use of a different substance) than new-onset users (Wiedemann et al, 2013). Potential risk of resuming drug use after surgery existed in patients who quit before surgery (Adams et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Altered fat regulation observed in cocaine-dependent men has been linked to lower levels of circulating leptin [79], lending support to the significance of hormones relative to addictive processes. Evidence that gastric bypass patients develop new-onset SUDs/AUDs in the post-surgical period (second year or later) suggests that “addiction transfer” is a likely phenomenon that may require specialized treatment [8082]. Interestingly, there is evidence of reduced appeal of high-energy foods in patients after gastric bypass [83] suggesting changes in brain reward that may be linked to alterations in gut microbiota.…”
Section: Substance Use Disorder (Sud)mentioning
confidence: 99%
“…This finding is particularly intriguing given the concept of “addiction transfer”, substituting one addiction to one substance to another (17, 18, 20, 35) in that such patients may be replacing the disordered use of food with marijuana. A possible explanation for these findings could be that patients who engage in current marijuana use satisfy the “addiction” with marijuana, thus not engaging in disordered eating behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that there are instances in which patients develop new onset substance use disorders after surgery, potentially substituting licit (i.e., alcohol, cigarettes) or illicit substances (i.e., drugs) for food (17-20) . It should be noted that general assumptions should not be made since individual differences among patients should be considered when determining who has the potential to become “addicted” to substances (21) , whether it be food or drugs.…”
Section: Introductionmentioning
confidence: 99%